Foreign Body Ingestion in Children Complicated by Duodenal Perforation: Case Report - Errami, Adil Ait; Najoua, Aballa; Aouroud, Hala; SIAD, Mohamed Ouled; Krati, Khadija (International Journal of Innovative Research in Medical Science, 2022)
Ingestion of a foreign body (FB) is a common accident among children. The majority of ingested foreign bodies are eliminated spontaneously and few of them leads to some rare but serious complication such as complication that requires urgent surgical management. In this article we report the case of an accidental nail ingestion in a 2 years old child complicated with a duodenal perforation. Emergency surgical care was performed, with nail removal and duodenal primary closure. The follow-up was uneventful and the recovery was smooth.